Analisis Perbandingan Kualitas Jaringan Internet 4G di Kampus UIN Suska Riau Menggunakan Metode Quality of Service - M. Fahrizal; Iwan Iskandar; Nazruddin Safaat Harahap; Reski Mai Candra (STMIK Budi Darma, 2023)
In the increasingly advanced digital era, the quality of internet networks has become a crucial factor in everyday life, particularly in academic environments such as campuses. The quality of 4G internet networks is also essential for students and staff in carrying out educational activities, research, and communication. Therefore, measuring and analyzing internet networks is necessary to ensure that the utilized network does not hinder activities that require internet access. This study explores the quality of 4G internet networks provided by three major providers, Smartfren, Telkomsel, and XL Axiata, at the UIN Suska Riau campus. The method used is Quality of Service (QoS), which measures four main parameters: throughput, packet loss, delay, and jitter. This research aims to provide comprehensive information regarding the quality of 4G networks offered by each provider within the campus environment. The measurement data indicates that XL Axiata performs the best in terms of throughput, with an average speed of 3843.8125 kbps and a